The Historicity of the Qur'an in Socio-Cultural of Arab Perspective - Muhamad Rifa’i Subhi (Jurnal Hikmatuna, 2017)
Most thinkers former Muslims are not able to escape the "sanctity" the text of the Qur’an, so that in researching the texts of the Qur’an they are not able to get out of the sanctity of the Qur’an as Allah's revelation. However, there are some Muslim scholars to position the text of the Qur’an as a text to be studied scientifically. Among these scientist is Khalil Abdul Karim, who explains that the Qur'an describes many stories of people who indicated earlier that Islam is not a new pure religion. Khalil Abdul Karim explained that the historicity contained in the Qur'an shows that the Islamic religion is closely related to the life or customs of the Arabs before Islam arrived. This article suggests that historicity of the Qur'an which is evidence that the majority of Islamic law derived from the Arabs in pre-Islamic Arab socio-cultural perspective study, thought Khalil Abdul Karim. Exploration data obtained from several sources, are analyzed using the content analysis, the process of decomposition of the data, drafting and preparation in a new way. The steps taken in the content analysis covering, open coding, axial coding, and selective coding.The results showed that the thought of Khalil Abdul Karim caused a variety of responses from various groups, both positive and negative responses. In analyzing the texts of the Qur’an, Khalil Abdul Karim use asbab al-nuzul rules who is no stranger to the science of the Qur'an. Khalil Abdul Karim takes a historical approach in their search, so the kind of thought saying that the tradition of pre-Islamic Arab tribes was the forerunner to the practice of sharia law, which includes worship, social, punishment, war and politics. In other words, Islam legalize the tradition of pre-Islamic Arab tribes as sharia law, either with or without slightest revision.